Pengembangan Instrumen Monitoring dan Evaluasi Layanan Praktikum di Laboratorium Fisika FKIP Universitas Tadulako - Muhammad Jarnawi; Syamsuriwal Syamsuriwal; Nurgan Tadeko (Universitas Tadulako, 2022)
The purpose of this study was to develop instruments for monitoring and evaluating practicum services in physics laboratories. This type of research is Research and Development (R&D) using the ADDIE model. Data collection was carried out through questionnaires and observation. Respondents in this study were lecturers, PLP, and students who were involved in carrying out practicums in physics laboratories. The instruments developed in this study were a satisfaction questionnaire for laboratory leaders, a student response questionnaire for laboratory staff services, a student satisfaction questionnaire for practicum services, a student response questionnaire for laboratory facilities and infrastructure, and a response questionnaire for practicum modules. The trial results show that the developed physics laboratory practicum service instrument has good quality and is suitable for use as a laboratory monitoring and evaluation instrument.